MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DALAM PEMBELAJARAN TEKS DESKRIPSI - Elfa Rahima; Faren Fiorenza; Khairunnas; Miftahul Hasanah; Nadiya Putri; Farel Olva Zuve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching descriptive texts at the junior high school level often faces challenges due to teacher-centered learning, which limits students’ active involvement and writing development. This study aims to describe the implementation of the Project Based Learning (PJBL) model in descriptive text instruction and to analyze students’ learning outcomes. This research employed a descriptive method with qualitative and quantitative approaches. The data consisted of daily assessment scores of descriptive writing from 32 ninth-grade students and were collected through documentation. Data analysis involved calculating the class average score and categorizing students’ achievement into low, medium, and high groups. The results showed that the class average score reached 89.97, indicating a good level of achievement. Most students were classified into the medium and high categories, while only a small number were in the low category. These findings indicate that Project Based Learning effectively supports students’ descriptive writing performance and learning achievement.